Empowerment of Cadres in Early Detection of Stunting Risk During Pregnancy - Elly Wahyuni; Mariati Mariati; Rialike Burhan; Ratna Dewi (Asosiasi Profesi Multimedia Indonesia, 2024)
In general, the aim of community service activities is to increase the knowledge of cadres and pregnant women about early detection of the risk of stunting as an effort to reduce the incidence of stunting. The method of implementing this service activity is carried out by forming a Stunting Care Cadre Group that can carry out early detection of stunting risk during pregnancy in Banjarsari Village, Enggano District, North Bengkulu Regency. In this activity, a pre-test, health education about early detection of stunting risk during pregnancy, after which a Post test was carried out to see if there was an increase in knowledge and skills of cadres in conducting early detection of stunting risk during pregnancy directly in pregnant women. As a result of training and cadre empowerment activities, there is an increase in the knowledge of stunting care cadre groups in Banjarsari Village, Enggano District with an average Pre-test score of 73.2 and an average Post-test score of 88.2, the average increase in knowledge score is an increase of 5.0 The implementation of Cadre Empowerment in Early Detection of Stunting Risk During Pregnancy, there is an increase in knowledge, the formation of an organizational structure of stunting care cadre groups in the village Banjarsari, Enggano District, North Bengkulu Regency. It is hoped that this community service activity can increase knowledge, skills and motivation for cadres and pregnant women to carry out Early Detection of Stunting Risk During Pregnancy.